Behavior of Atta sexdens rubropilosa (Hymenoptera: Formicidae) workers during the preparation of the leaf substrate for symbiont fungus culture - De Andrade, Ana Paula P. [UNESP]; Forti, Luiz Carlos [UNESP]; Moreira, Aldenise A. [UNESP]; Boaretto, Maria Aparecida C. [UNESP]; Ramos, Vânia M. [UNESP]; De Matos, Carlos Alberto O. [UNESP] (My University, 2002)
The behavioral repertory of Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae) workers marked by size category was studied during the preparation of the leaf substrate in the laboratory. The workers were marked according to three physical castes, i.e., minima, generalist and forager. Seven types of behavioral acts were recorded for each caste, with the following frequencies: licking leaf fragments (64.6%), holding fragments on the surface of the fungus garden (16.4%), shredding the fragments (6.0%), chewing and crimping the edges of the fragments (9.0%), incorporating the fragments (2.7%), touching the surface of the fungus with their mandibles and other mouthparts after incorporation (0.3%), and depositing fecal fluid (0.1%). The minima workers were found to be more specialized in the activities related to the preparation of the leaf substrate, which represented 52% of the total number of tasks performed. The generalists performed 40.3% of these tasks, and the foragers 7.9%. Licking the substrate was the behavior most frequently recorded and performed for a longer period of time. In this way, the workers may feed and at the same time eliminate microorganisms that are harmful to the symbiont fungus. The smaller castes, minima and generalists, are those most responsible for the preparation of the leaf substrate and predominate within a colony. From a practical viewpoint, with the introduction of toxic bait containing insecticides, for example, these size categories will be those most intensely intoxicated, especially through the behavior of licking bait pellets. On the basis of the data obtained about these behaviors, we may raise the hypothesis that trophallaxis in not the major factor triggering contamination with an insecticide among the workers of a colony.
Keywords: Atta sexdens rubropilosa; Behavior; Castes; Leaf-cutting ants; Substrate preparation; Atta sexdens